Mathematics

Question

System of equation by using substitution
3=y+3x
-x+3y=29

1 Answer

  • Answer:

    x=-2

    y=9

    Step-by-step explanation:

    3=y+3x ---- A

    -x+3y=29 ----B

    step 1. rearrange equation A, so you have the "y" variable on one side

    3=y+3x

    -3x     -3x

    3-3x=y

    y=3-3x ---- C

    step 2. Substitute equation C into equation B in place of "y"

    -x+3(3-3x)=29 ---foil

    -x+9-9x=29 -- collect like terms

    -10x+9=29

           -9     -9

       -10x=20

          ÷-10     ÷-10

             x=-2

    Step 3. Substitute x=-2 into equation C to find y

    y=3-3(-2)

    y=3+6

    y=9

    Check you answer by subsituting x=-2 and y=9 back into equation A and B

NEWS TODAY